Benralizumab, an anti-interleukin-5 receptor α monoclonal antibody, as add-on treatment for patients with severe, uncontrolled, eosinophilic asthma (CALIMA): a randomised, double-blind, placebo-controlled phase 3 trial. Issue 10056 (29th October 2016) - FitzGerald, J Mark; Bleecker, Eugene R; Nair, Parameswaran; Korn, Stephanie; Ohta, Ken; Lommatzsch, Marek; Ferguson, Gary T; Busse, William W; Barker, Peter; Sproule, Stephanie; Gilmartin, Geoffrey; Werkström, Viktoria; et al.
Summary: Background: Benralizumab is a humanised, afucosylated, anti-interleukin-5 receptor α monoclonal antibody that induces direct, rapid, and nearly complete depletion of eosinophils. We aimed to assess the efficacy and safety of benralizumab as add-on therapy for patients with severe, uncontrolled asthma and elevated blood eosinophil counts. Methods: In this randomised, double-blind, parallel-group, placebo-controlled, phase 3 study (CALIMA) undertaken at 303 sites in 11 countries, we enrolled patients aged 12–75 years with severe asthma uncontrolled by medium-dosage to high-dosage inhaled corticosteroids plus long-acting β₂-agonists (ICS plus LABA) and a history of two or more exacerbations in the previous year. Patients were randomly assigned (1:1:1) to receive 56 weeks of benralizumab 30 mg every 4 weeks (Q4W), benralizumab 30 mg every 8 weeks (Q8W; first three doses 4 weeks apart), or placebo (all subcutaneous injection). Patients were stratified (2:1) by baseline blood eosinophil counts 300 cells per μL or greater and less than 300 cells per μL, respectively. Patients and study centre staff were masked to treatment allocation. The primary endpoint was annual exacerbation rate ratio versus placebo for patients receiving high-dosage ICS plus LABA with baseline blood eosinophils 300 cells per μL or greater (intention-to-treat analysis). Key secondary endpoints were pre-bronchodilator forced expiratory volume in 1 s (FEV1 ) and total asthma symptom score. This study is registered withClinicalTrials.gov, numberNCT01914757 . Findings: Between Aug 21, 2013, and March 16, 2015, 2505 patients were enrolled, of whom 1306 patients were randomised; 425 patients were randomly assigned to and received benralizumab 30 mg Q4W, 441 to benralizumab 30 mg Q8W, and 440 to placebo. 728 patients were included in the primary analysis population. Benralizumab resulted in significantly lower annual exacerbation rates with the Q4W regimen (rate 0·60 [95% CI 0·48–0·74], rate ratio 0·64 [95% CI 0·49–0·85], p=0·0018, n=241) and Q8W regimen (rate 0·66 [95% CI 0·54–0·82], rate ratio 0·72 [95% CI 0·54–0·95], p=0·0188, n=239) compared with placebo (rate 0·93 [95% CI 0·77–1·12], n=248). Benralizumab also significantly improved pre-bronchodilator FEV1 (Q4W and Q8W) and total asthma symptom score (Q8W only) in these patients. The most common adverse events were nasopharyngitis (90 [21%] in the Q4W group, 79 [18%] in the Q8W group, and 92 [21%] in the placebo group) and worsening asthma (61 [14%] in the Q4W group, 47 [11%] in the Q8W group, and 68 [15%] in the group). Interpretation: Benralizumab significantly reduced annual exacerbation rates and was generally well tolerated for patients with severe, uncontrolled asthma with blood eosinophils 300 cells per μL or greater. Our data further refine the patient population likely to receive the greatest benefit from benralizumab treatment. Funding: AstraZeneca and Kyowa Hakko Kirin.